STUDY ON INCLUSION OF PROBIOTIC, PREBIOTIC AND ITS COMBINATION IN BROILER DIET AND THEIR EFFECT ON GROWTH PERFORMANCE OF COMMERCIAL BROILERS - Saiyad, MA; Joshi, RS; Savaliya, FP; Patel, AB; Mishra, RK; Bhagora, NJ (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Day-old commercial broiler chicks (n = 200) were distributed randomly into 5 dietary treatment groups, viz. control (T1), probiotic in the feed @ 100 g/tonne (T2), prebiotic in the feed @ 500 g/ tonne of feed (T3), synbiotic (probiotic + prebiotic) @ 100 g/tonne and 500 g/tonne of feed, respectively (T4) and synbiotic (probiotic + prebiotic) @ 50 g/tonne and 250 g/tonne of feed (T5) respectively, and up to 6 weeks of age their performance was evaluated weekly. Results revealed that various feed additives used in the study affected the growth and feed efficiency of chicks significantly (P < 0.05). Body weight at the end of starter phase and whole experiment showed that all treatment groups gained significantly (P
Keywords: Broiler; Performance; Prebiotic; Probiotic; Synbiotic